Degradasi Zat Warna Metil Merah Dengan Katalis ZnO Menggunakan Metode Fotosonolisis - Putri Ayu; Ananda Putra; Hary Sanjaya; Indang Dewata; Yohandri Yohandri (Jurnal Periodic Jurusan Kimia UNP, 2021)
The research that has been carried out on the photosonolytic degradation of methyl red uses a ZnO as a catalyst which aims to determine the effect of time and catalyst mass on the degradation of methyl red. The time of degradation is about 30 to 150 minutes while about 0,05 grams to 2,5 grams of catalyst mass is used. The measurement results of the Uv-Vis spectrophotometer were obtained at a wavelength of 435nm with an absorbance 0,2471. In the variation of the degradation time, the highest result was obtained at 60 minutes which was 75,27%, while the ZnO mass variation carried out at the optimum time of 60 minutes obtained the highest results in the addition of 0,15 grams ZnO with the percentage of degradation (%D) of 47,79%. This study shown that hydroxyl radicals (∙OH) takes as a main control in degrading of methyl red.